2018
DOI: 10.1080/07448481.2018.1431915
|View full text |Cite
|
Sign up to set email alerts
|

Mental health consequences of sexual assault among first-year college women

Abstract: The occurrence of sexual assault early in college has adverse mental health consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 38 publications
3
71
1
Order By: Relevance
“…Both the unadjusted and adjusted ORs describing the association between sexual violence and mental health outcomes, specifically anxiety, depression, eating disorders, insomnia, stress, and suicidal ideation, were statistically significant. The results were consistent with other findings that sexual violence has an adverse impact on mental health (Brewer et al 2018;Carey et al 2018;Chang et al 2015;Kelley and Gidycz 2019;Rimsza et al 1988;Stephens and Wilke 2016).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Both the unadjusted and adjusted ORs describing the association between sexual violence and mental health outcomes, specifically anxiety, depression, eating disorders, insomnia, stress, and suicidal ideation, were statistically significant. The results were consistent with other findings that sexual violence has an adverse impact on mental health (Brewer et al 2018;Carey et al 2018;Chang et al 2015;Kelley and Gidycz 2019;Rimsza et al 1988;Stephens and Wilke 2016).…”
Section: Discussionsupporting
confidence: 92%
“…This effect is attributed to the stigma of sexual violence and subsequent self-blame (Herman 1992;Jordan et al 2014;Resick 1993). Research has examined sexual violence among college students, along with the psychiatric implications, ranging from depression to dietary disorders (Brewer et al 2018;Carey et al 2018;Chang et al 2015;Kelley and Gidycz 2019;Leone and Carroll 2016;Stephens and Wilke 2016). In the past decade, universities have experienced increased sexual violence reporting rates and Title IX complaints, potentially due to the Obama administration's more proactive stance on Title IX enforcement (Musu-Gillette et al 2017;Wilson 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of such association remains unclear, but multiple perspectives, from genetics to environmental influences such as imitation or socioeconomic family adversities, are likely (Brent & Melhem, ). In recent years, sexual assaults in college campuses are of growing interest (Carey, Norris, Durney, Shepardson, & Carey, ; Fedina, Holmes, & Backes, ; Halstead, Williams, & Gonzalez‐Guarda, ). Also, mood, anxiety, and substance use disorders have been associated with SI (Brent et al., ) and these disorders are the most common focus of college suicide prevention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with 873 female college students, 22% reported experiencing IPV or SV during the preceding semester (Sutherland, Fantasia, Hutchinson, & Katz, 2017). The adverse health outcomes of IPV and SV are numerous and well-documented and include: physical injuries and death, higher rates of gynecological health issues and unintended pregnancy, gastrointestinal and neurological issues, chronic pain, posttraumatic stress disorder and other mental health issues including anxiety and depression (Campbell, 2002;Carey, Norris, Durney, Shepardson, & Carey, 2018;Feltner et al, 2018;Moyer, 2013b;Potter, Howard, Murphy, & Moynihan, 2018). Potter et al (2018) found that more than 90% of college women who experienced SV reported health problems related to their assault; many also experienced academic challenges and disruptions in studies due to their SV experience and/or subsequent health problems.…”
Section: Violence Experiences In College Womenmentioning
confidence: 99%